Coal and Gas - From Cradle to Grave with Carbon Capture and Storage - Arne Steinkraus (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2015)
Existing studies on Carbon Capture and Storage (CCS) only focus on costs and carbon dioxide (CO2 ) reduction that arise at the power plant and geological storage. These studies do not consider additional expenses and emissions at the input and output pathways. Consequently, we use a simulation model containing input data from different studies to estimate the cradle-to-grave costs of avoided carbon dioxide. We show that the true costs vary between 70 and 90 US-Dollars per ton of CO2 . Additional sensitivity analyses support the results because they are robust against different parameter adjustments. Because it is not evident whether CCS is an efficient mitigation option, it is compared to a variety of renewable energy sources. Thus, it is cheaper to avoid one ton of CO2 by means of wind energy, but costs arising from the use of solar energy are much higher.
Keywords: Q40; Q50; 330; CCS; Cradle-to-Grave; climate change; coal; gas; efficiency analysis; Effizienzanalyse; Treibhausgas-Emissionen